Ajaran Tattwa Dalam Tutur Medang Kemulan - Sandi Untara, I Made Gami; Wika Krishna, Ida Bagus (Kamaya: Jurnal Ilmu Agama, 2023)
Medang Kemulan's speech is one of the many speeches containing the teachings of Shiva. Judging from the language used and the sloka texts contained in it, it appears that the Medang Kemulan lontar is an old lontar. Tutur Medang Kemulan not only teaches about the teachings of wariga (kala or time) but also emphasizes the teachings of philosophy (Tattwa), namely ethics and human philosophy applied in community life. Tutur Medang Kemulan also teaches about regulating social institutions, especially Balinese society, which is widely discussed. Apart from being an understanding of the prohibition of incestuous marriage, Tutur Medang Kemulan also contains Hindu religious teachings, the aim of which is to realize human social life with individuals who are virtuous in accordance with the teachings of religious literature. Apart from that, in Tutur Medang Kemulan the teachings of self-control regarding human life are taught, namely a person's ability not to do things that are not good or appropriate. In general, this research aims to find out and understand the philosophical teachings (Tattwa) and time (kala) contained in the Medang Kemulan Tutur so that it can be used as a guide by Hindus and the wider community and motivated to understand more deeply the concept of life as a human contained in the Medang Tutur Glory. This type of research is qualitative research. The data source used is primary data sourced from literature/libraries. Data collection techniques were carried out using library methods. This research uses data analysis methods with qualitative descriptive techniques. The concept of Tattwa teachings is about the essence, truth and philosophy of life contained in Tutur Medang Kemulan, such as the concepts of social institutions, ethics, self-control and love.